INVESTIGATING STUDENTS’ EXPECTATIONS OF THE LECTURERS’ STYLES IN TEACHING ENGLISH - Diana Achmad; Asnawi Muslem; Tia Rahmanita; Humaira Irfan Khan (English Review: Journal of English Education, 2023)
The teaching style is the way the lecturer delivers material and controls students’ activities in the classroom. Teachers have their own teaching style depending on personal and students’ needs. Meanwhile, the students have their own expectations regarding the teachers’ styles of teaching English as well. This research investigated the university students’ expectations of the lecturers’ styles in teaching English. It used descriptive quantitative and qualitative methods as the research design. The data were collected by distributing a questionnaire to 45 students and interviewing 9 of them who were randomly chosen from the students majoring in English at one of the universities in Banda Aceh, Indonesia. The quantitative data were analyzed statistically, while the qualitative data were analyzed through data condensation, data display, and conclusion. The results of the research revealed that the dominant lecturer’s style expected by the students in teaching English is the combination of facilitator, personal model, and expert styles. The students favored the lecturers who facilitate students’ learning activities, give personal examples, and provide detailed information that students need. If the lecturers used only one teaching style, the students said they would get bored and learning would not reach maximum results. The combination of the three styles is a form of the student-centered model in which students play an active role in the learning activity in the classroom.